Understanding the Inter-Ethnic Solidarity Formation in A Plural Charismatic Community - Rizabuana Ismail; Grace Prima Apriani Sihombing; Ria Manurung; Sismudjito Sismudjito; Henry Sitorus (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
This study describes the inter-ethnic solidarity in the charismatic Mawar Sharon church in Medan City, Indonesia, also known as the Connect Group Church.The qualitative and ethnographic approaches were used to determine the solidarity in Charismatic Churches where people are separated by ethnicity. Data were collected through in-depth interviews with respondents actively involved in the activities of the religious connect groups, such as sponsors, coaches, and team leaders. The results showed that the activities in the community include fellowship, ice breakers, praise and worship, and material sharing as a form of learning about inter-ethnic solidarity among members. Furthermore, active members such as team leaders, sponsors, and coaches play significant roles in these activities. Meanwhile, music and church songs are used to strengthen the relationship between members.